Attention performance among Brazilian truck drivers and its association with amphetamine use: pilot study - Lucio Garcia de Oliveira; Bernardo dos Santos; Priscila Dib Goncalves; Heraclito de Barbosa Carvalho; Eduardo Massad; Vilma Leyton (Universidade de São Paulo, 2013)
The aim of this article was to describe the attention functioning of twenty-two truck drivers and its relationship with amphetamine use. Those drivers who reported using amphetamines in the twelve months previous to the interview had the best performance in a test evaluating sustained attention functioning. Although amphetamine use may initially seem advantageous to the drivers, it may actually impair safe driving. The findings suggest the importance of monitoring the laws regarding amphetamine use in this country.